presidential decree no.148/2013 concerning the issue of the customs tariff = قرار رئيس جمهورية مصر العربية رقم 184 لسنة 2013 بإصدار التعريفة الجمركية / Presidency - Egypt. Presidency (2025)
Decree the President of the Arab Republic of Egypt No. 184 of the Year 2013 concerning the issue of the customs Tariff قرار رئيس جمهورية مصر العربية رقم 184 لسنة 2013 بإصدار التعريفة الجمركية